Efficacy of mandibular advancement devices in two patients with moderate obstructive sleep apnea: Case reports - Filiz Keyf; Güliz Aktaş; İhsan Keyf (Cumhuriyet University, 2015)
Mandibular advancement device (MAD) can be used as a treatment alternative on apnea and sleep in moderate obstructive sleep apnea. Polysomnographic sleep studies were performed on two patients before and about 1 year after continuous use of the MADs. The results were compared. In the first case, the apnea-hypopnea index (AHI) before treatment was 22.0 and decreased, to 4.3, after 1 year of treatment. The AHI after 1 year of usage differed significantly from the pretreatment value. In the second case, the AHI before treatment was 21.4 and decreased to 10.1 after 1 year of treatment. The 1-year clinical evaluation showed preserved dental status, preserved action of the masticatory muscles, and preserved function of the temporomandibular joint. The MADs reduced apneas and improved sleep quality in patients with obstructive sleep apnea, especially in those with mild or moderate disease.